Analysis on a composite B-pillar crashworthiness and occupant safety for side impact in sedan car - Abeba, Tsegay (ASTU, 2019)
Drivers And Passengers Which Involved In Side Impact Collisions Have High Tendency To Fatal Injuries Compared To Frontal Or Rear Impact Collisions Due To Limited Space In The Passenger Compartment. The Passengers Are Subjected For Different Kinds Of Injuries; Mainly Brain Injuries Caused Due To The Intrusion Of B-Pillar Inside The Passenger Cabin; Through Collision With The Head Of The Occupant At The Same Time, Due To Different Environmental Conditions Such As Fuel Consumption And Emission, It Is Essential To Decrease The Structural Weight Of The Vehicle. The Objective Was To Analyze A Composite B-Pillar For Minimum Deformation And Weight. This Improves The Vehicle Crashworthiness And Ensuring The Safety Of Passenger During Side Crash Accident. The B-Pillar Was Designed Following The Standard Methods And Validated According To Euroncap And Iihs. In This Thesis Hyper Mesh, Hyper Crash, Madymo And Ls Dyna Were Adopted For Finite Element Analysis Of A Ford Taurus B-Pillar. To Select The Composite Thickness And Orientation, This Study Initially Analyzes The B-Pillar After Being Subjected To An Even Force Of 140 Kn. This Resulted The Selected B-Pillar With Thickness T = 4.15mm Decrease In Deformation Up To 78.2 % And T=2.9mm Up To 42.4% Compared To The Minimum B-Pillar Thickness T=1.6mm. The Degree Of Orientation Was Set As 0??, 45??, 0??, 45??, 0??, 45??, 0??, 45??, And 0 ??. The 1.1 Kg Composite B-Pillar Shows Decrease In Weight Up To 57.9 % Compared To 2.6 Kg Steel B-Pillar. To Ensure That Euroncap Tp Directives Were Met, Both Steel And Composite Pillars Were Merged With The Vehicle And Crashed Into 254mm Diameter Rigid Pole At A Speed Of 29 Km/H. Composite B-Pillar Showed 62.5 Mj Energy Absorbing Capacity Which Increases By 50.4 % Compared With Steel B-Pillar Results 29.8 Mj. The Composite And Steel Pillars Resulted In A Deformation Of 399.4 Mm And 579.1 Mm Respectively, Which Decrease In Deformation Up To 31.1 %. To Ensure The Occupant Safety Hybrid Iii 50th Percentile Dummy Were Used. Composite B-Pillar Resulted In Head Injury Criterion (Hic) Thoracic Trauma Index (Tti) And Pelvic Acceleration Of 263g??S, 15g??S And 75g??S Respectively That Is 72.9 %, 62.5 % And 37.5 % Less Than Steel Pillar. This Decreases The Injury Level Of The Passenger. This Showed An Improvement In The Energy Absorption And Occupant Safety And Decrease In Weight And Deformation Which Can Save Passengers From Injury And Also Fuel Consumption.
Keywords: side impact, crashworthiness, B-pillar, steel, composite, hyper mesh, MADYMO, TTT,HIC